1992
DOI: 10.1007/bf00180968
|View full text |Cite
|
Sign up to set email alerts
|

Growth of transformed roots in a nutrient mist bioreactor: reactor performance and evaluation

Abstract: A nutrient mist bioreactor was modified for culturing transformed roots of Beta vulgaris and Carthamus tinctorius on a nylon support. Culture conditions of misting cycle, inoculum size, batch or continuous operation and sucrose concentration were varied in order to maximize growth over a 1-week period. Root tissue cultured in nutrient mists in a 1.8-1 culture chamber achieved levels of growth equivalent to hairy roots cultured in shake flasks with identical medium. Our resuits demonstrate the effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 11 publications
2
31
1
Order By: Relevance
“…result indicates that estimation of root growth based on weighing of a drained reactor (e.g., DiIorio et al, 1992aDiIorio et al, , 1992b could be in error by as much as 30-100%. Root morphology, extent of root hair formation, presence of gas down-flow, and bioreactor configuration will all contribute to differences in static hold-up.…”
Section: Liquid Hold-upmentioning
confidence: 95%
“…result indicates that estimation of root growth based on weighing of a drained reactor (e.g., DiIorio et al, 1992aDiIorio et al, , 1992b could be in error by as much as 30-100%. Root morphology, extent of root hair formation, presence of gas down-flow, and bioreactor configuration will all contribute to differences in static hold-up.…”
Section: Liquid Hold-upmentioning
confidence: 95%
“…In gas-phase reactors, roots are exposed to air and liquid nutrients are either sprayed onto the roots (Flores and Curtis, 1992;Singh and Curtis, 1994;Williams and Doran, 2000) or delivered as a mist of micron-sized droplets (Buer et al, 1996;DiIorio et al, 1992a;Weathers et al, 1999). Gasphase reactors can virtually eliminate any oxygen deficiency in dense root beds (Weathers et al, 1999) while also providing a low shear stress environment.…”
Section: Introductionmentioning
confidence: 99%
“…CO 2 -enriched nutrient mist cultures of Carthamus tinctorius and Beta vulgaris hairy roots showed increased growth versus control cultures that were fed ambient air [60]. However, a similar effect was not observed in hairy roots of Artemisia annua.…”
Section: Mist Reactors For Hairy Root Culturecontrasting
confidence: 55%
“…Liu et al [69] provided gas either only when mist was not being generated, or continuously; while Weathers et al [5] provided gas only when the mist was provided. Interestingly, DiIorio et al [60] also observed that hairy roots seemed to have optimum mist duration for growth. Their studies with hairy roots of Beta vulgaris and Carthamus tinctorius showed that either increasing or decreasing the "off" time beyond a certain limit adversely affected root growth of those species.…”
Section: Mist Deposition Modellingmentioning
confidence: 95%
See 1 more Smart Citation